2022
DOI: 10.53730/ijhs.v6ns6.10743
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Yoga on the anxiety level of pregnant women in the third trimester during the COVID-19 pandemic in Purbalingga, Indonesia

Abstract: Introduction: Prenatal yoga is a modified type of Hatha yoga that is adjusted to the condition of pregnant women. This study aims to determine the effect of prenatal yoga on the anxiety level of pregnant women in the third trimester during the Covid-19 pandemic in Purbalingga. Methods: This study used Pre-Experimental Design with One Group Pretest-Posttest Design. The sample in this study was 576 pregnant women in clinics in Purbalingga. It used the total sampling technique. Data analysis used univariate and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…To enhance the flow of blood throughout the body. (7) Prenatal yoga comprises several exercises, such as centering, belly breathing, warming up, Cow position, Cat Pose, child position, and relaxation. (7) The study's findings (1) show the impact of engaging in prenatal yoga on diminishing anxiety levels throughout the third trimester of pregnant mothers.…”
Section: Health Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance the flow of blood throughout the body. (7) Prenatal yoga comprises several exercises, such as centering, belly breathing, warming up, Cow position, Cat Pose, child position, and relaxation. (7) The study's findings (1) show the impact of engaging in prenatal yoga on diminishing anxiety levels throughout the third trimester of pregnant mothers.…”
Section: Health Dynamicsmentioning
confidence: 99%
“…(7) Prenatal yoga comprises several exercises, such as centering, belly breathing, warming up, Cow position, Cat Pose, child position, and relaxation. (7) The study's findings (1) show the impact of engaging in prenatal yoga on diminishing anxiety levels throughout the third trimester of pregnant mothers. Maidina Putri's study revealed a 10.1% reduction in anxiety among primigravida pregnant women in their third trimester.…”
Section: Health Dynamicsmentioning
confidence: 99%